Assessment of efficacy of Anti-IgE (Omalizumab) therapy in patients with severe allergic asthma in a tertiary care hospital of Eastern India - Saswata Ghosh; Prosenjit Gayen; Animesh Mandal; Ramtanu Bandyopadhyay (International Journal of Medical Research and Review, 2019)
Introduction: Immunoglobulin E dependent mechanisms play an important role in the development of airway inflammation in allergic asthma. Atopic patients with severe asthma frequently have poorly controlled disease. Many have poor asthma control despite intensive treatment. Severe allergic asthma patients frequently treated with oral corticosteroids and therefore may develop serious side-effects. Anti-IgE antibody had been used in severe persistent allergic asthma in Western countries. However, its long-term efficacy in patients in India has not been reported.Objective: To assess the efficacy of anti IgE therapy in patients with severe allergic asthma.Method: 30 (16 male and 14 female) patients, with mean age of 49 having severe persistent allergic asthma, with recurrent exacerbations and on oral/IV steroids, received Omalizumab 150mg/300mg/450 mg for 1 year. Total dose of oral Steroids, use of rescue medications, changes in lung function (FEV1) were recorded at the baseline, 16 weeks & at end of the treatment (52 weeks) and then analyzed.Results: Significant reduction observed in total oral steroid use at 16 week & at 52 weeks. -10.5mg (p<0.003) & 22.5mg respectively. Use of rescue medications decreased by -7.90 puffs(p- <0.001) at 16 weeks and by -13.67 puffs (13.67 (p -<0.001) at 52 weeks. Improvements in lung Function (FEV1) observed with a tune of 700 ml. from Baseline after 52 weeks therapy.Conclusion: Use of anti-IgE antibody for 1 year is well tolerated and led to an overall significant improvement in patients with severe persistent allergic asthma.